2022
DOI: 10.1093/cercor/bhac273
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation to the angular gyrus modulates the temporal dynamics of the hippocampus and entorhinal cortex

Abstract: Transcranial magnetic stimulation (TMS) delivered to the angular gyrus (AG) affects hippocampal function and associated behaviors (Thakral PP, Madore KP, Kalinowski SE, Schacter DL. Modulation of hippocampal brain networks produces changes in episodic simulation and divergent thinking. 2020a. Proc Natl Acad Sci U S A. 117:12729–12740). Here, we examine if functional magnetic resonance imaging (fMRI)-guided TMS disrupts the gradient organization of temporal signal properties, known as the temporal organization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Consistent with findings from our previous work (Bouffard, Golestani et al, 2023; Coughlan et al, 2023), we found that data-driven clustering of the signal voxel autocorrelation in TLE patients and controls resulted in three distinct clusters. Our clustering approach does not use a predefined number of clusters, and visual examinations of the cluster maps revealed that there were no differences in number of clusters between patients and controls, nor was there a difference between healthy and epileptogenic hemispheres.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with findings from our previous work (Bouffard, Golestani et al, 2023; Coughlan et al, 2023), we found that data-driven clustering of the signal voxel autocorrelation in TLE patients and controls resulted in three distinct clusters. Our clustering approach does not use a predefined number of clusters, and visual examinations of the cluster maps revealed that there were no differences in number of clusters between patients and controls, nor was there a difference between healthy and epileptogenic hemispheres.…”
Section: Discussionsupporting
confidence: 92%
“…In this study we examined single voxel autocorrelation and clusters of single voxel autocorrelation in patients with unilateral left and right TLE to investigate how hippocampal damage present in TLE affects the temporal signal dynamics in the hippocampus. Here, we replicated our past work (Bouffard, Golestani et al, 2023; Coughlan et al, 2023) and found that all groups demonstrated a pattern of high autocorrelation values clustered in the anterior-medial hippocampus and low autocorrelation values clustered in the posterior-lateral. There were two major findings in the TLE groups, both selective to the anterior-medial cluster.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One promising candidate that may contribute to insight-driven memory reconfiguration is the angular gyrus. The angular gyrus has extensive structural and functional connections to many other brain regions (Petit et al, 2023), including the hippocampus (Coughlan et al, 2023; Uddin et al, 2010). Accordingly, previous studies have shown that stimulation of the angular gyrus resulted in altered hippocampal activity (Thakral et al, 2020; Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%